Sodium homeostasis with chronic sodium loading in preascitic cirrhosis. Issue 6 (1st December 2001) - Wong, F; Liu, P; Blendis, L
Abstract : BACKGROUND: Preascitic cirrhotic patients receiving 200 mmol of sodium daily for seven days remain in positive sodium balance. Thereafter, sodium handling is unknown. AIM: To assess renal sodium handling in preascitic cirrhosis on a high sodium diet for five weeks. METHODS: Sixteen biopsy proven preascitic cirrhotics were assessed at weekly intervals for five weeks on a diet of 200 mmol sodium/day using a daily weight diary and weekly 24 hour urinary sodium estimations. Fasting supine neurohormone levels were measured at baseline and weekly for five weeks while haemodynamics were measured at baseline and at five weeks. RESULTS: The daily diet of 200 mmol of sodium resulted in weight gain and a positive sodium balance for three weeks, associated with significant suppression of plasma renin activity and aldosterone levels, and a significant rise in plasma atrial natriuretic peptide levels (p<0.05). Patients' weights plateaued during week 4, associated with complete sodium balance and significant suppression of plasma noradrenaline levels (p<0.05). This was followed by a negative sodium balance and weight loss, and finally complete sodium balance, again despite a mean net gain of 2.3 (0.3) kg, associated with a return of plasma renin activity and aldosterone levels to within normal ranges. The lack of increase in central blood volume in addition to the persistent increase in plasma atrial natriuretic peptide levels indicated that residual volume expansion, consequent to persistent weight gain, was distributed on the venous side of the circulation. No free fluid was seen on repeat abdominal ultrasound after five weeks. CONCLUSION: Preascitic cirrhotics have a natriuretic "escape" after three weeks on high sodium dietary intake, associated with elevated plasma atrial natriuretic peptide levels and suppression of the renin-angiotensin-aldosterone system. With continued suppressed sympathetic activity, preascitics re-establish complete sodium balance but with a net weight gain and presumed increased intravascular volume, but without ascites. This further elucidates the compensated sodium retaining abnormality that characterises preascitic cirrhosis.